Progressive Lower Extremity Weakness and Axonal Sensorimotor Polyneuropathy from a Mutation in KIF5A (c.611G>A;p.Arg204Gln) - Nivedita U. Jerath; Tiffany Grider; Michael E. Shy (Case Reports in Genetics)
Introduction. Hereditary Spastic Paraplegia (HSP) is a rare hereditary disorder that primarily involves progressive spasticity of the legs (hamstrings, quadriceps, and calves). Methods. A 27-year-old gentleman was a fast runner and able to play soccer until age 9 when he developed slowly progressive weakness. He was wheelchair-bound by age 25. He was evaluated by laboratory testing, imaging, electrodiagnostics, and molecular genetics. Results. Electrodiagnostic testing revealed an axonal sensorimotor polyneuropathy. Genetic testing for HSP in 2003 was negative; repeat testing in 2013 revealed a mutation in KIF5A (c.611G>A;p.Arg204Gln). Conclusions. A recent advance in neurogenetics has allowed for more genes and mutations to be identified; over 76 different genetic loci for HSP and 59 gene products are currently known. Even though our patient had a sensorimotor polyneuropathy on electrodiagnostic testing and a 2003 HSP genetic panel that was negative, a repeat HSP genetic panel was performed in 2013 due to the advancement in neurogenetics. This revealed a mutation in KIF5A.